Green and chemical-free process of enzymatic xylooligosaccharide production from corncob: Enhancement of the yields using a strategy of lignocellulosic destructuration by ultra-high pressure pretreatment - Phisit Seesuriyachan (2018)
© 2017 Elsevier Ltd In this study, the pressures at 50–500 MPa were evaluated at different time to pretreat and further enzyme hydrolysis. The ultra-high pressure (UHP) pretreatment at 100 MPa for 10 min led to improved accessibility of enzyme for conversion of xylan to xylooligosaccharide (XOS). The maximum XOS yield of 35.6 mg/g substrate was achieved and firstly reported at 10% (w/v) of substrate, 100 U of endo-xylanase/g corncobs and incubation time of 18 h. The enzymatic hydrolysis efficiency was increased by 180.3% and released a high amount of xylobiose. The UHP pretreatment relatively did not affect to the composition of corncob, but decreased 34.3% of lignin. Interestingly, antioxidant activities of XOS using UHP pretreatment were higher than untreated corncob. The UHP pretreatment improved lignocellulosic destructuration and XOS yields in a shorter time without the need of chemicals, implying that UHP could be an effective pretreatment of biomass with a chemical-free process.